2012
DOI: 10.1371/journal.pone.0046403
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Evolutionary Dynamics and Information Content of the Avian Mitochondrial Control Region and ND2 Gene

Abstract: Mitochondrial DNA is an important tool for inference of population history in animals. A variety of mitochondrial loci have been sampled for this purpose, but many studies focus on the non-coding D-loop or control region (CR), which in at least some species appears hypermutable. Unfortunately, analyses of this region are sometimes complicated by segmental duplications, as well as by difficulties in sequencing through repeat expansions, driving many researchers to favor single-copy protein-coding or ribosomal R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 116 publications
1
22
0
Order By: Relevance
“…ND6 and eight tRNAs are transcribed from the light strand (L), however the other 12 PCGs, 14 tRNAs, two rRNAs, and two noncoding region (CR, CCR) genes are located on the heavy (H) strand. The gene arrangement pattern of the G. himalayensis mitochondrial genome is identical to that in genera Aegypius , Buteo, and Falco , all which have the remnant CCR gene order, but differ from the standard bird gene order (Barker, Benesh, Vandergon, & Lanyon, ; Gibb et al, ; Li, Huang, et al, ). The G. himalayensis mitogenome nucleotide composition is biased toward A and T (56.14%: A = 224.55%, T = 29.49%, G = 14.37% and C = 31.59%), which is similar to that seen in the other Gyps mitogenomes (52.71%–57.65%; Table ; Haring et al, ).…”
Section: Resultsmentioning
confidence: 79%
“…ND6 and eight tRNAs are transcribed from the light strand (L), however the other 12 PCGs, 14 tRNAs, two rRNAs, and two noncoding region (CR, CCR) genes are located on the heavy (H) strand. The gene arrangement pattern of the G. himalayensis mitochondrial genome is identical to that in genera Aegypius , Buteo, and Falco , all which have the remnant CCR gene order, but differ from the standard bird gene order (Barker, Benesh, Vandergon, & Lanyon, ; Gibb et al, ; Li, Huang, et al, ). The G. himalayensis mitogenome nucleotide composition is biased toward A and T (56.14%: A = 224.55%, T = 29.49%, G = 14.37% and C = 31.59%), which is similar to that seen in the other Gyps mitogenomes (52.71%–57.65%; Table ; Haring et al, ).…”
Section: Resultsmentioning
confidence: 79%
“…The 61 WMG dataset (25) contained 363 single-nucleotide polymorphisms (SNPs), of which 154 were potentially phylogenetically informative, with 62 (17%) located in the rapidly evolving CR (32). Bayesian and maximum likelihood inference analyses of the WMG dataset supported the haplogroup framework defined by Liu et al (24) and Miao et al (25) and, importantly, produced robust support for haplogroups A-G and Z (i.e., haplogroups where multiple individuals were sequenced), as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While some studies question using a highly variable marker like control region versus ND2 or cytochrome b for phylogeographic and phylogenetic studies, previous work has shown that this marker can be used to resolve deep splits in evolutionary history among avian species (Barker, Benesh, Vandergon, & Lanyon, ) and of corvids in particular (Saunders & Edwards, ). Within a single species, some loci may not be variable enough to detect differences between populations (e.g., cytochrome b (Steeves, Anderson, McNally, Kim, & Friesen, ) versus control region (Steeves, Anderson, & Friesen, ) in masked boobies ( Sula dactylatra )).…”
Section: Discussionmentioning
confidence: 99%